Enhancement using CIRCLE software post cornea lenticule extraction for advanced refractive correction - Gitansha S Sachdev; Tasneem Neemuchwala; Shreyas Ramamurthy (Indian Journal of Ophthalmology, 2025)
Purpose: To report visual outcomes of enhancement after corneal lenticular extraction for advanced refractive correction (CLEAR, Femto LDV) using the CIRCLE software (Carl Zeiss Meditec, Germany). Methods: A prospective interventional study included eyes undergoing enhancement for under-correction or regression following CLEAR; at least three months after the primary procedure. CIRCLE software (pattern D) was used to convert the initial cap into a flap, which was subsequently raised and the stromal bed was ablated using an excimer laser (Zeiss Mel 90), with a Plano target in all eyes. Safety and visual outcomes at the three months postoperative visit were analyzed, with maximum follow-up till one year. Results: Nine eyes of six patients were included in the data analysis. The mean preoperative refractive spherical equivalent treated using the CLEAR software was −5.04 ± 2.28 diopter (D). Enhancement was performed for a mean residual error of −0.86 ± 0.54 D. The CIRCLE procedure was performed 6.67 ± 1.79 months after the primary procedure and resulted in a final manifest spherical equivalent of − 0.01 ± 0.04 D at the three months postoperative visit (P = 0.001867). Mean uncorrected distance visual acuity (UDVA) improved from logMAR 0.31 ± 0.11 to 0.01 ± 0.03 (P = 0.0008). Post-enhancement UDVA of 20/20 or better was achieved in 78% of the eyes. None of the eyes reported loss of lines in corrected distance visual acuity (CDVA). No intraoperative complications were noted in the cohort. No incidence of epithelial ingrowth, regression, or stromal haze was noted up till one year postoperative visit. Conclusion: CIRCLE software may be considered as an optional treatment modality for enhancement following CLEAR.